2020
DOI: 10.1111/ijpo.12719
|View full text |Cite
|
Sign up to set email alerts
|

Show or tell: Children's learning about food from action vs verbal testimony

Abstract: Summary Background Childhood obesity continues to be a critical health concern in the United States. Nonetheless, interventions that focus on delivering verbal lessons about food and health to children in preschool classrooms have had only modest effects. Objectives The present study examines the relative effectiveness of showing vs telling children about food to promote healthy eating, with a focus on unfamiliar foods and vegetables. Methods Three‐ to six‐year‐old children (n = 71) were tested in a laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Previous research has shown that children learn a great deal from direct communication (DeJesus & Venkatesh, 2020; Harris & Koenig, 2006; Harris et al, 2018; Heyman & Gelman, 1999; Rhodes, 2012; Stephens & Koenig, 2015). However, children also learn from observations of other people’s interactions.…”
Section: The Current Studymentioning
confidence: 99%
“…Previous research has shown that children learn a great deal from direct communication (DeJesus & Venkatesh, 2020; Harris & Koenig, 2006; Harris et al, 2018; Heyman & Gelman, 1999; Rhodes, 2012; Stephens & Koenig, 2015). However, children also learn from observations of other people’s interactions.…”
Section: The Current Studymentioning
confidence: 99%
“…In a comprehensive review on experimental studies that seek to change children's eating behavior, 29 of the 120 studies reviewed used weighed food intake as a dependent variable (among other common outcomes, such as food preferences or choices which will be described in the upcoming sections), specifically for studies that sought to increase children's fruit and vegetable intake (see DeCosta et al, 2017 for review). Many of our own studies take this approach, including studies that examine how social knowledge of the food influences children's food intake (DeJesus et al, 2018b), whether children eat more food if they assisted in preparing the food (DeJesus et al, 2019a), how maternal talk and intake of food relates to children's intake of those foods (DeJesus et al, 2018a), and whether children learn about food by verbal testimony or by seeing someone eat that food (DeJesus and Venkatesh, 2020). When this in-person interaction is not possible, it is harder for researchers to use pre-post weight measurements as a standardized measure of food intake given the access to and variability of weighing scales that families may have at home.…”
Section: Measuring Children's Food Intakementioning
confidence: 99%